Estrutura das assembleias de peixes de trechos de riachos submetidos a diferentes graus de urbanização na região de Londrina-PR - Marcucci, Cristian Roberto (2016)
Small orders aquatic environments integrate various physical, chemical and biological processes of their surroundings, thus are directly influenced by the use and occupation pattern of the basin, being heavily pressured by urban occupation. The impacts generated by this occupation tend to cause the decline of species diversity, modifying the pattern of fish assemblages. The aim of this study was evaluate the diversity patterns of fish assemblages in streams excerpts under different degrees of urbanization. The streams excerpts analyzed belongs to the basins of Cambé, Cafezal and Taquara streams, in the Londrina region. Through GIS, the excerpts landscape was classified into five units: dense vegetation, agriculture / field, bare soil, sealed area and water surface. Fish were sampled by manual and electric fishing in three sampling sites along a longitudinal gradient on a quarterly basis from 2013 to 2014. The limnology parameters such as electrical conductivity, turbidity, pH and dissolved oxygen were also measured during the samplings. The landscape units, limnology parameters and diversity were related through a principal component analysis. According to the landscape impervious percentage, the Cambé stream is placed in a higher urbanized area, as well as the site 1 sub-basin of Cafezal stream. The sites with greater influence of urbanization showed higher conductivity, which may indicate the presence of pollutants. The Taquara stream, which has a smaller urban area, showed greater similarity of the richness and diversity between the sampling sites, while the other streams presented variation of richness, diversity and evenness. The sites under urban influence had fewer Characiformes and Siluriformes species and dominance of exotic species, tolerant to disturbances in the environment. The Principal Component Analysis segregate the sampled sites, revealing strong relationship between urbanization, electrical conductivity and percentage of individuals of the species Poecilia reticulata. This analysis also showed that sites with smaller urban influence have higher richness and diversity, favoring the predominance of Characiformes and Siluriformes species naturally more abundant in neotropical streams.